Economic empowerment of the pilot reintegration program for female genital fistula survivors in Kenya during the COVID-19 pandemic - Mary Ann McCammon; Norah Amisi Otondo; Nancy Kay (Frontiers Media S.A., 2022)
ObjectiveTo determine whether a pilot reintegration program for female genital fistula survivors that included a combination of financial support, psychosocial support, and mentoring would result in their long-term economic empowerment during the COVID-19 pandemic.ResultsNine fistula survivors participated in a 29-month pilot reintegration program offered by Kenya Quilts for Empowerment (KQFE), a registered Community Based Organization in Kenya. Originally, the program was intended to last for 18 months, but as a result of the pandemic, this was extended to achieve the long-term economic empowerment of women. The program was based on best practices for poverty alleviation that included multiple sources of income, psychosocial support, and mentoring, sustained over the entire 29-month period. All the women were severely impoverished at the baseline assessment, with one having some savings, and a few having productive assets, which were primarily chickens. Financial training and an initial non-refundable cash transfer provided start-up funds for small businesses; these initially flourished before floundering during the pandemic and eventually recovering. Funds were also used to buy livestock. A key component of the program was the provision of national health insurance for each woman and her family, which helped them stay healthy without having to sell any income-generating livestock. Other key components were the psychosocial support and mentoring provided within their support group. After 29 months, every woman had achieved long-term economic empowerment and "graduated" to become a KQFE ambassador, tasked with identifying fistula survivors within their communities, and referring them for surgery and participation in a reintegration support group.